Renal tubular P-glycoprotein expression is reduced in plasma cell disorders - Cihan Heybeli; Mehmet Asi Oktan; Hayri Ustun Arda; Serkan Yildiz; Mehtat Unlu; Caner Cavdar; Aykut Sifil; Ali Celik; Sulen Sarioglu; Taner Camsari (The Korean Society of Nephrology, 2019)
Background : P-glycoprotein (P-gp) transports many chemicals that vary greatly in their structure and function. It is normally expressed in renal proximal tubular cells. We hypothesized that P-gp expression influences light chain excretion. Therefore, we investigated whether renal tubular P-gp expression is altered in patients with plasma cell disorders. Methods : We evaluated renal biopsy specimens from patients with plasma cell disorders (n = 16) and primary focal segmental glomerulosclerosis (the control group, n = 17). Biopsies were stained with an anti-P-gp antibody. Loss of P-gp expression was determined semi-quantitatively. Groups were compared for loss of P-gp expression, and clinical variables. Results : P-gp expression loss was more severe in patients with plasma cell disorders than it was in those with glomerulonephritis (P = 0.021). In contrast, clinical and histological parameters including serum creatinine, level of urinary protein excretion, and interstitial fibrosis/tubular atrophy grade were not significantly different between the groups. P-gp expression loss increased with age in patients with plasma cell disorders (P = 0.071). This expression loss was not associated with serum creatinine, the level of urinary protein excretion or the interstitial fibrosis/tubular atrophy grade. There was no significant association between the severity of P-gp expression loss with the types and serum levels of light chains, isotypes and serum immunoglobulin levels. Conclusion : Renal tubular P-gp expression is significantly down-regulated in patients with plasma cell disorders characterized by nephrotic range proteinuria. Additional studies are needed to determine whether reintroduction of renal tubular P-gp expression would mitigate the proximal tubular injury that is caused by free-light chains.